(untitled) (KIUT Publication, 2025)
In the context of intensifying environmental challenges and the need for sustainable economic growth, the development of small business and private entrepreneurship based on the principles of the "green economy" is of particular importance. The emphasis is placed on the rational use of natural resources, the introduction of energy- and resource-saving technologies, environmental management of production, and the promotion of "green" innovations.